Orthodontic post-adjustment pain control with acupuncture - Boleta-Ceranto,Daniela de Cassia Faglioni (2014)
OBJECTIVE: This study aimed to evaluate the analgesic efficacy of systemic acupuncture therapy on the pain caused after orthodontic adjustments. METHODS: An initial sample of 30 orthodontic patients with fixed appliances monthly adjusted was selected; however, only 11 participants completed the study. For this reason, final sample comprised these patients' data only. Initially, average pain levels were assessed at different periods by means of an analogue visual scale (VAS) for three months without acupuncture. In the following three months, the volunteers were submitted to systemic acupuncture sessions on Hegu (LI4) and Jiache (St6) points,before orthodontic adjustments were carried out. RESULTS: Results revealed statistically significant reduction in pain level indexes both for men (P = 0.030) and women (P = 0.028) when acupuncture therapy was performed prior to orthodontic adjustment. Patients did not present any side effects. CONCLUSION: Acupuncture is a safe and effective method in reducing orthodontic post-adjustment pain.